Dinamika Dakwah Dalam Perspektif Komunikasi - Tomi Hendra (IAIN Padangsidimpuan, 2019)
Abstract: Da'wah and communication have a very strong relationship, especially in the development of Islam as a referee of the process of improving the people. It is undeniable that in order to improve the Ummah from all the problems that have occurred, it is necessary to handle and the right way in conveying the message of da'wah. In order to realize good propaganda, a preacher must be able to master good communication. Communication has an important role in conveying da'wah messages so that there will be a shift and change in honey for the realization of amar makruf nahi mungkar. This paper aims to explore the dynamics of da'wah in a communication perspective. Communication as the main key in conveying the message of da'wah, but in some practice the da'wah material is not well received by madu due to the communication of da'I itself Keywords: Da'wah Dynamics in Communication PerspectiveabstrakDakwah dan komunikasi mempunyai hubungan yang sangat kuat khususnya dalam perkembangan Islam sebagai wasilah terhadap proses perbaikan umat. Tidak bisa dipungkiri bahwa untuk memperbaiki umat dari sekian persoalan yang terjadi, maka hal ini sangat diperlukan penanganan dan cara yang tepat di dalam menyampaikan pesan dakwah. Demi mewujudkan dakwah yang baik, maka seorang da’í harus mampu menguasai komunikasi yang baik. Komunikasi memiliki peran penting di dalam menyampaikan pesan-pesan dakwah agar terjadi pergeseran dan perubahan pada mad’u demi terwujudnya amar makruf nahi mungkar. Tulisan ini bertujuan untuk mengupas dinamika dakwah dalam perspektif komunikasi. Komunikasi sebagai kunci utama di dalam menyampaikan pesan dakwah, namun dalam beberapa prakteknya materi dakwah tidak diterima dengan baik oleh mad’u yang disebabkan oleh komunikasi da’I itu sendiri Kata kunci: Dinamika Dakwah Dalam Perspektif Komunikasi